Experimental demonstration of a free-space cylindrical cloak without superluminal propagation - Xu, Su (2013)
We experimentally demonstrated an alternative approach of invisibility cloaking that can combine technical advantages of all current major cloaking strategies in a unified manner and thus can solve bottlenecks of individual strategies. A broadband cylindrical invisibility cloak in free space is designed based on scattering cancellation (the approach of previous plasmonic cloaking), and implemented with anisotropic metamaterials (a fundamental property of singular-transformation cloaks). Particularly, nonsuperluminal propagation of electromagnetic waves, a superior advantage of non-Euclidian-transformation cloaks constructed with complex branch cuts, is inherited in this design, and thus is the reason of its relatively broad bandwidth. This demonstration provides the possibility for future practical implementation of cloaking devices at large scales in free space.